Hierarquia social e sucesso alimentar em callithrix jacchus (Primates, Callithrichidae), sob condições naturais - Dias, Derlan Angelim (2007)
The competition for resources is one of the costs of group living. The scramble competition is considered an indirect type of competition, mainly associated with factors like group size and distribution of resources. Contest competition occurs when individuals compete directly for resources. In species that exibit this type of competition the establishment of dominance hierarchy can occur, resulting in differences on feeding and reproductive benefits for each member of the group. In these cases, aggressive and submissive behaviors are expected as a way to signal social status. The aim of this study was to investigate the effects of social hierarchy over food ingestion in Callithrix jacchus. Data recording was from September/2006 to March/2007, eight days by month, at Floresta Nacional de Açu do Instituto Chico Mendes de Biodiversidade. The observation time started at 05:00 AM and finished after the last animal was on the sleeptree. Analyses of aggressive interactions, behavioral profile and diet, reveals a lot of advantages for dominat animals in the study group. Dominant individuals had higher intake of animal matter that subordinates. The last ones, consumed fruits, exsudate and, eventually, explored itens that were not common to the diet. We suggest that dominance hiearchy enable the reproductive female to assure priority on access to food resources, a important caracteristc to supply tha costs to maintain tha high reproductive taxa of the specie. We also suggest that reproductive male, due to the participation on food transfer, had the forage efficience reduced